O NOVO DESENVOLVIMENTISMO E A NOVA FACE DAS POLÍTICAS COMPENSATÓRIAS - Alba Tereza B. de Castro (Revista de Políticas Públicas, 2013)
The work sets up the new face of compensatory policies in Brazil which, according to the ideals of the new developmentalism, broadens its range of extension, although it remains in their focused and minimalist dimensions. The seeming contradiction of this movement mirrors the popu- lation roots of liberalism in an alleged new model of “humanized capitalism”. The strong ideological content of co-optation and economic strategy is embedded in this scenario where the assistance widens and has the centrality as a mechanism for poverty management.